The incorporation of children to the practice of Handball in the community Villa Rosa of Venezuela - Alfredo Izquierdo-Hernández; Rogelio García-Vulgar (Universidad de Guantánamo, 2012)
This paper is aimed at children's motivation to the practice of Handball as a sports for all the community in the municipality Villa Rosa of García municipality of the State Nueva Esparta in the Bolivar´s Republic of Venezuela; it was carried out with the aim of offering an additional option for youngsters to use their free time developing a system of physical recreational activities according to their pleasure and preferences. A diagnosis applied demonstrated that the activities being offered before did not correspond with the interests of youngsters, since they lacked motivational and appealing activities.